Bovine Liver Glutamate Dehydrogenase: Tentative Amino Acid Sequence; Identification of a Reactive Lysine; Nitration of a Specific Tyrosine and Loss of Allosteric Inhibition by Guanosine Triphosphate - Smith, Emil L. (1970)
A tentative but almost complete amino acid sequence for the subunit peptide chain of bovine liver glutamate dehydrogenase indicates a minimal size of 506 residues with a molecular weight of 56,100, in accord with the physical size of the subunit of 55,900. Inactivation with pyridoxal 5′-phosphate, followed by reduction with sodium borohydride, has permitted identification of the essential lysine as residue 97. Nitration of tyrosine-412 is accompanied by loss of the allosteric inhibitory effect of guanosine triphosphate. Comparison of the sequences of glutamate dehydrogenase and glyceraldehyde-3-phosphate dehydrogenase has indicated that only two 12-residue sequences are similar in the two enzymes; this sequence includes reactive lysine-97 of the former enzyme.